SENTIMENT MARKET ANALYSIS ON REPLACEMENT ANNOUNCEMENT OF CHIEF EXECUTIVE OFFICER (CEO) - Novyandri Taufik Bahtera (TIJAB (The International Journal of Applied Business), 2017)
This study examines the market reaction to the announcement of Chief Executive Officer (CEO) measured by abnormal return. The study sample consisted of 55 CEO turnover announcements using the t-test to test information content of the announcement. The author groups the changes into two factors: (1) change process (routine and non-routine) and (2) substitute origin (inside and outside). The market reacts significantly positively to the announcement of CEO turnover routinely with the origin of the replacement from inside (inside) the company. Different reactions occur in the announcement of routine outside and non-routine insidediary CEO turnover where announcements are responded negatively and significantly. The market does not react to the announcement of non routine outside CEO changes. These results show that investors in Indonesia react positively to routine CEO turnover inside because investors believe that new CEOs will continue their strategy and leadership style and have lower levels of uncertainty. Negative reactions to routine outside CEO turnover are caused by the market belief that the successor will not continue the previous CEO's strategy and has a high degree of uncertainty. The cause of a negative market reaction to the announcement of a non-routine inside CEO turnover is that a replacement CEO will continue the old leadership style and jointly be responsible for the company's poor performance.